Client And Coalitions dalam Implementasi Kebijakan Kesehatan Ibu dan Anak di Kabupaten Kupang - Rene, Mariayani; -, Kismartini; Purnaweni, Hartuti (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2019)
One important factor that determines the successful implementation of mother and child policy is support from community especially the community whose be the target of the polices (clients) and also certain parties (coalitions) who have an interest in the policy. This paper aims to find clients and coalitions in the implementation of health mothers and children in Kupang Regency, which is one of the regions in Indonesia with the highest infant mortality cases. The method used is descriptive qualitative, by using one indicator in Najam implementation models, namely client and coalitions for analysis. The results of the study show that the implementation of Perda No 3 of 2016 as maternal and child health policy in Kupang Regency has not received support from the community, especially those who are the client of the policy. Therefore, it is recommended that the Kupang Regencial Government increase the socialization to the people in particular who are the clients of this policy